The role of trade-led economic growth in fostering development: Lessons for the post-2015 development agenda - Shishir Priyadarshi; Trineesh Biswas (World Trade Organization (WTO), 2014)
This essay reviews the historical and ongoing role played by trade in sustained high growth and human development progress, and makes the case that the post-2015 development agenda should include considerations related to trade rules and supply-side capacity. Given the strong links between trade-led growth, economic upgrading, and poverty reduction, the paper argues that trade led economic growth must be prioritised in the post-2015 development agenda.
Keywords: O1; O4; N4; 330; UN; Millennium Development Goals; Post-2015 Development Agenda; GATT WTO; trade; growth; development